2012
DOI: 10.2174/138161212803530880
|View full text |Cite
|
Sign up to set email alerts
|

Stress Response Regulation in Panic Disorder

Abstract: Panic disorder is a frequent and disabling mental disorder characterized by recurrent periods or abrupt surges of intense fear or discomfort, the panic attacks. The clinical phenomenology of panic attacks suggests a prominent role of a disturbed stress response regulation in the aetiopathology of this disorder. We summarize the results of challenge tests of the hypothalamus-pituitary-adrenocortical (HPA) axis in panic disorder and give an overview of studies using psychosocial challenge paradigms. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Our finding of increased A 1 AR availability in risk allele carriers is in line with these findings and suggestions. Stress response regulation including HPA axis activation is altered in panic disorder patients (recent review by Ising et al, 2012) and sleep deprivation occurs with negative mood and increased anxiety up to catastrophizing in them (Kahn et al, 2013). Notably, these consequences of sleep deprivation are greater after the presentation of a mild stressor, possibly due to a lowered psychological threshold to estimate a situation as stressful (Minkel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of increased A 1 AR availability in risk allele carriers is in line with these findings and suggestions. Stress response regulation including HPA axis activation is altered in panic disorder patients (recent review by Ising et al, 2012) and sleep deprivation occurs with negative mood and increased anxiety up to catastrophizing in them (Kahn et al, 2013). Notably, these consequences of sleep deprivation are greater after the presentation of a mild stressor, possibly due to a lowered psychological threshold to estimate a situation as stressful (Minkel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, PD patients exhibit an increased coupling of feedback-evoked EEG amplitude and heart rate changes than healthy individuals ( Mueller et al, 2014 ), which has previously been shown to be an indicator of neuro-visceral connectivity ( Mueller et al, 2010a ). Regarding the physiological stress axes, PD patients do not differ from healthy individuals in baseline morning or diurnal cortisol release or negative feedback sensitivity ( Ising et al, 2012 ), but they show blunted cortisol responses to psychosocial stress ( Petrowski et al, 2010 , 2013 ). In terms of SAM axis activity existing studies have yielded mixed findings.…”
Section: Synthesis Of Findings On Interoception and Stressmentioning
confidence: 99%
“…PD is a common psychiatric disorder with a complex etiology that likely involves multiple genes in addition to nongenetic influences. 22 , 23 , 24 , 25 , 26 , 27 Many previous studies have identified associations between BDNF polymorphisms and psychiatric disorders. Associations have been found between the BDNF 196G/A (rs6265) polymorphism and chronic depression, 28 treatment response in patients with major depression, 29 and Alzheimer's disease, 30 , 31 although findings have not always been consistent.…”
Section: Discussionmentioning
confidence: 99%